Design of a Tri-Wheel Handling Trolley. - Tumusiime Charles (Kabale University, 2023)
Now-a-days simple mechanical devices like hand trolleys with single and dual wheel are finding their use in large number of industries as well as fur household purposes. But their usage is limited to carry goods along the floors from one location to the other. Out of the formulated designs that are available in the market, no design fulfils the need of support in shifting the load over stairs. To eliminate this difficulty, stair wheels (combination of three wheels) are used as a substitute which will reduce the effort of lifting. The report focuses on the design of a tri-wheel stair climbing hand trolley to move along rough surfaces and to transport considerable loads over stairs with the improved wheel arrangement, with comparatively less human effort & manufacturing cost. The design concerns including steepness of the stairs, steadiness and speed of the trolley while climbing the stairs are discussed. Hybrid trolleys such as tri wheeled ones can be adopted to carry several items at various locations where mechanical elevators cannot be installed.